(untitled) (Research, Society and Development, 2021)
Objective: to measure the knowledge and preparation of 3rd and 4th year nursing and 5th and 6th year medical students at FAMERP, regarding the initial care of burn victims, to find out what health care students know about the initial care of burn patients. Methodology: Cross-sectional study with descriptive design, quantitative approach of the analytical type with correlation between variables. Information from 71 records was collected through the application of three questionnaires: (questionnaire 1. Initial care to the burned - personal interest and previous contact; questionnaire 2a) Questions about initial care to the burned - nursing; questionnaire 2b) Questions about initial care to the burned - medicine) all with closed questions, destined to the area of knowledge of each course on the treated subject, applied to 53 students of the third and fourth years of nursing and 18 students of the internship of medicine, in model form of the platform google forms, sent online. Subsequently, the data were tabulated and analyzed. Results: Nursing students demonstrated knowledge considered average regarding the initial care of the burned patient, while medical students demonstrated low knowledge. Conclusion: Students do not have sufficient knowledge regarding the initial care of burned patients, and there are great difficulties and uncertainties when approaching the theme.